2018
DOI: 10.1155/2018/3168320
|View full text |Cite
|
Sign up to set email alerts
|

Excitation-Dependent Fluorescence Quantum Yield for Freshwater Chromophoric Dissolved Organic Matter from Northern Russian Lakes

Abstract: Advanced fluorescence analysis within the wide range of excitation wavelengths from 230 to 510 nm accompanied with chromatography was used to study natural chromophoric dissolved organic matter (CDOM) from three freshwater Karelian lakes. The influence of excitation wavelength (λex) on fluorescence quantum yield and emission maximum position was determined. The CDOM fluorescence quantum yield has reached a minimum at λex∼270–280 nm and a maximum at λex∼340–360 nm. It was monotonously decreasing after 370 nm to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Considering such systems as simple models of natural water containing DOM, the obtained results can provide new information concerning fluorescence monitoring of DOM in surface water systems. In DOM fluorescence monitoring, the spectral band λ em of 300–350 nm serves as a marker of the presence of tryptophan-like components or protein-like fractions in water [ 6 , 7 , 28 ]. The established correlation between fluorescence and nanoassociates’ parameters ( Figure 2 and Figure 8 ) indicates that this band also reflects the presence of a dispersed phase in water, formed mainly by ordered structures such as EZ-water [ 35 ], and bioorganic substances of different structures in low concentrations, as a rule, below 1 × 10 −8 mol/L.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering such systems as simple models of natural water containing DOM, the obtained results can provide new information concerning fluorescence monitoring of DOM in surface water systems. In DOM fluorescence monitoring, the spectral band λ em of 300–350 nm serves as a marker of the presence of tryptophan-like components or protein-like fractions in water [ 6 , 7 , 28 ]. The established correlation between fluorescence and nanoassociates’ parameters ( Figure 2 and Figure 8 ) indicates that this band also reflects the presence of a dispersed phase in water, formed mainly by ordered structures such as EZ-water [ 35 ], and bioorganic substances of different structures in low concentrations, as a rule, below 1 × 10 −8 mol/L.…”
Section: Resultsmentioning
confidence: 99%
“…Works [ 28 , 30 , 31 , 32 , 33 , 34 , 35 ] also show the presence of similar absorption bands in the UV spectra of natural water, diluted aqueous solutions of some BACs, and systems containing structured water (EZ-water) in contact with a hydrophilic surface. Excitation in this UV region causes fluorescence in two spectral ranges of 300–350 and 400–450 nm.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The fluorescence spectrum of the S-24 system had a different band shape with the maximum in the region of 312–325 nm. This suggests that the nature of the structures formed at high dilutions differs from the nature of domains and nanoassociates formed, as a rule, in the 1·10 −4 –1·10 −18 M range ( Sedlák, 2006 ; Sedlák and Rak, 2013 ; Elia et al, 2014 ; Ryzhkina et al, 2018a ; Ryzhkina et al, 2018b ; Patsaeva et al, 2018 ; Ryzhkina et al, 2019 ; Ryzhkina et al, 2020 ), i.e., capable of containing a certain amount of solute ( Ryzhkina et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, and for the first time, it was established that the rearrangement of nanoassociates at certain low critical concentrations is accompanied not only by a significant change in physicochemical properties and bioeffects but also in the UV absorption in the 200–300 nm range ( Ryzhkina et al, 2018a ; Ryzhkina et al, 2018b ). Works ( Lobyshev et al, 1999 ; Chai et al, 2008 ; Elia et al, 2014 ; Elia et al, 2018 ; Patsaeva et al, 2018 ) have demonstrated the presence of absorption within the range of 200–350 nm in the UV spectra of natural water, aqueous solutions of BAS, and systems containing structured water in contact with a hydrophilic surface. Excitation in this region results in fluorescence within two spectral ranges: 300–350 and 400–450 nm.…”
Section: Introductionmentioning
confidence: 99%